2017
DOI: 10.1128/jcm.02559-16
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Rapid Herpes Simplex Virus PCR Assay on Duration of Acyclovir Therapy

Abstract: Herpes simplex virus (HSV) infections of the central nervous system (CNS) are associated with significant morbidity and mortality rates in children. This study assessed the impact of a direct HSV (dHSV) PCR assay on the time to result reporting and the duration of acyclovir therapy for children with signs and symptoms of meningitis and encephalitis. A total of 363 patients with HSV PCR results from cerebrospinal fluid (CSF) samples were included in this retrospective analysis, divided into preimplementation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 42 publications
(41 reference statements)
3
14
0
Order By: Relevance
“…Our results suggest that the implementation of rapid molecular testing for meningoencephalitis in pediatric hospitals can lead to earlier optimization of empiric therapy, as seen in several recent studies [26][27][28][29]. However, in contrast to our study, these reports refer to single PCR assays.…”
Section: Discussionmentioning
confidence: 43%
“…Our results suggest that the implementation of rapid molecular testing for meningoencephalitis in pediatric hospitals can lead to earlier optimization of empiric therapy, as seen in several recent studies [26][27][28][29]. However, in contrast to our study, these reports refer to single PCR assays.…”
Section: Discussionmentioning
confidence: 43%
“…However, data supporting the benefit of molecular RDTs in these cases are scarce. Using a retrospective quasi-experimental study design, Van and colleagues [20] recently described the effect of switching from the realStar alphaherpesvirus PCR kit, a multiplex PCR LDT that detects HSV-1, HSV-2, and varicella zoster virus, (alTona Diagnostics, Hamburg, Germany) that was performed once per day, 6 days per week, to the Simplexa HSV 1 and 2 Direct assay, which was performed on demand, 24 hours per day, 7 days per week. This study did not report any positive results, but among their 182 patients with suspected meningitis and/or encephalitis who were tested prior to rapid testing and 181 patients tested post-implementation, the study reported a decrease in the median duration of acyclovir therapy from 29.2 hours to 14.3 hours.…”
Section: Rdts In Meningitis and Encephalitismentioning
confidence: 99%
“…This study did not report any positive results, but among their 182 patients with suspected meningitis and/or encephalitis who were tested prior to rapid testing and 181 patients tested post-implementation, the study reported a decrease in the median duration of acyclovir therapy from 29.2 hours to 14.3 hours. The authors felt that, given evidence that renal toxicity and neurotoxicity typically occur within the first 48 hours of intravenous acyclovir administration, this reduction in acyclovir use associated with rapid HSV-1/HSV-2 testing had the potential to be clinically impactful [20].…”
Section: Rdts In Meningitis and Encephalitismentioning
confidence: 99%
“…CSF analysis reveals lympho-monocytic pleocytosis, slightly increased protein levels and HSV-positive polymerase chain reaction [38][39][40].…”
Section: Viral Infectionsmentioning
confidence: 99%